Facilitating TiB2 for filtered vacuum cathodic arc evaporation - Brzezinka, Tomasz L.; Rao, Jeff; Paiva, Jose M.; Azkona, Ibon; Kohlscheen, Joern; Fox-Rabinovich, German S.; Veldhuis, Stephen C.; Endrino, José L. (MDPI, 2020)
TiB2 is well established as a superhard coating with a high melting point and a low coefficient of friction. The brittle nature of borides means they cannot be utilised with arc evaporation, which is commonly used for the synthesis of hard coatings as it provides a high deposition rate, fully ionised plasma and good adhesion. In this work, TiB2 conical cathodes with non-standard sintering additives (carbon and TiSi2) were produced, and the properties of the base material, such as grain structure, hardness, electrical resistivity and composition, were compared to those of monolithic TiB2. The dependence of the produced cathodes’ electrical resistivity on temperature was evaluated in a furnace with an argon atmosphere. Their arc–evaporation suitability was assessed in terms of arc mobility and stability by visual inspection and by measurements of plasma electrical potential. In addition, shaping the cathode into a cone allowed investigation of the influence of an axial magnetic field on the arc spot. The produced cathodes have a bulk hardness of 23–24 GPa. It has been found that adding 1 wt% of C ensured exceptional arc-spot stability and mobility, and requires lower arc current compared to monolithic TiB2. However, poor cathode utilization has been achieved due to the steady generation of cathode flakes. The TiB2 cathode containing 5 wt% of TiSi2 provided the best balance between arc-spot behaviour and cathode utilisation. Preventing cathode overheating has been identified as a main factor to allow high deposition rate (±1.2 µm/h) from TiB2-C and TiB2-TiSi2 cathodes.
Keywords: TiB2; TiB2-C; TiB2-TiSi2; SEM; EDS; XPS; milling; aluminium